Mapping the research landscape of mHealth and technology in pediatric chronic illness: a bibliometric study - Rodríguez-Jiménez, Esther; Martín-Ávila, Javier; Valero-Moreno, Selene; Pérez-Marín, Marián (Frontiers in Digital Health, 2025)
IntroductionThe presence of a chronic disease during adolescence has been linked to an increased risk of developing psychosocial problems and a greater likelihood of experiencing difficulties during the transition to adulthood. In this regard, research has been conducted on the development of applications or programs based on new technologies to address the potential complications associated with self-management and coping with chronic diseases in adolescents.MethodThe objective of the present study was to conduct a bibliometric analysis of the existing literature on the use of new technologies to enhance self-management and coping with chronic diseases during adolescence. This four-staged bibliometric analysis was conducted using the following software programs: HisCite, Bibexcel, Pajek, and VOSviewer. The programs were utilized for the extraction of data and the subsequent construction of graphs, which facilitate the visualization of existing networks between disparate authors, institutions, and terms.ResultsThe screening results shortlisted a total of 157 articles from an initial 207. The further analysis of these records indicated that the United States was the most prominent nation in terms of scientific output in the domain of digital applications designed to enhance self-management and coping in chronic diseases during adolescence.DiscussionThe digital intervention in this specific population is primarily associated with the development of the mHealth app, along with the physical and psychological consequences that illness can entail. This research can serve as a reference for future bibliometric studies or scientific investigations in this field.